Blockchain-Integrated HR Analytics for Improved Employee Management - Dhameliya, Niravkumar; Mullangi, Kishore; Shajahan, Mohamed Ali; Sandu, Arun Kumar; Khair, Md Abul (ABC Journal of Advanced Research, 2020)
This study aims to understand better how blockchain-integrated HR analytics may improve staff management practices in businesses. The study’s primary goals are to determine how blockchain technology affects HR procedures, analyze its effects on worker performance, and determine how policies will be affected by its adoption. The paper examines the incorporation of blockchain technology into HR analytics by synthesizing case studies, industry reports, and current literature through a secondary data-based review technique. The main conclusions are improved data security and integrity, streamlined ingenious contract procedures, open decision-making, performance management based on data, and encouraging employee accountability and ownership. Addressing technological complexity, regulatory obstacles, interoperability problems, energy consumption issues, and data access and control problems are some policy consequences. To leverage the benefits of blockchain technology in HRM, policymakers are advised to provide clear regulatory frameworks, invest in technical support and training, and investigate long-term, privacy-preserving solutions. Blockchain-integrated HR analytics present a viable way for businesses to enhance staff management plans and promote organizational efficacy in the digital age.